Proposta de taxa de manejo dos resíduos sólidos urbanos gerados no município de São João Batista do Glória – MG - Wenceslau, Gilson de Oliveira (2015)
Despite the guidelines established by the Leis de Saneamento Básico and the Política Nacional de Resíduos Sólidos, there is a great difficulty for municipalities to promote the proper management of municipal solid waste (MSW) due to the expenses of each step of the process. However, several cities in Brazil face technical and financial difficulties for not knowing how to calculate the rate of solid waste in towns with up to 20,000 inhabitants, especially considering the principle that the polluter should pay. In this context lies the city of São João Batista do Glória, MG, which has not established a calculation system for billing rate or MSW management fee yet. Therefore, considering that the management fee of municipal solid waste is an important tool for recovering management costs, this study sought to present a proposal using the methodology suggested by some authors, with adjustments and adaptations to the reality of São João Batista do Glória, MG. Thus, aiming at drafting a proposal for MSW management fee for that municipality, it was necessary to diagnose the generation of MSW, the collection system (conventional and selective) and the system of Screening and Composting Unit (UTC). Based on surveys on collection operation costs (selective and conventional), treatment and disposal of São João Batista do Glória's MSW, it was possible to offer a value to the management fee of solid waste for the city of this study. The proposed value for solid waste management fee is R$ 15.25 economy month-1 and to calculate it, collection operation costs (selective and conventional), treatment and disposal as well as the need for an investment in MSW management structure to a 20 year horizon were considered.